Clinical characteristics and surgical outcomes in thoracic outlet syndrome: a comparative study of cases with and without cervical rib - Amr N. Ali; Hesham ElSobky; El-Sayed Abou El-Magd; Abdel Wahab Mahmoud Ibrahim (Egyptian Journal of Neurosurgery)
Abstract Background Thoracic outlet syndrome (TOS) is a complex neurovascular condition caused by the compression of structures within the thoracic outlet. The presence of a cervical rib adds an additional layer of complexity, influencing the clinical presentation, progression, and outcomes. This study aims to evaluate the differences in clinical characteristics and treatment outcomes between patients with and without a cervical rib. Methods This prospective study was conducted over one year and included 19 patients diagnosed with symptomatic TOS. Patients were divided into two groups: group A (11 patients without cervical rib) and group B (8 patients with cervical rib). All patients underwent thorough clinical evaluation, including history taking, physical examination, imaging studies, and electrophysiological tests. Pain levels were assessed using a visual analog scale before and after operation as well as recording intraoperative data and postoperative complications. Results Patients with cervical ribs (group B) presented at a younger age (25.38 years of age in group B vs. 37.09 years of age in group A) were more likely to exhibit bilateral affection (37.5% in group B vs. 9.1% in group A) and exhibited more severe and rapidly progressing symptoms (The mean duration of symptoms in group B is 9.91 months vs. 27.5 months in group A.) compared to patients without cervical rib (group A). Surgical intervention in group B resulted in more rapid and complete symptom resolution with morbidity rates comparable to group A. Conclusions Cervical rib-associated TOS presents distinct challenges requiring tailored diagnostic and therapeutic approaches. Surgical management offers superior outcomes in this subgroup, emphasizing the importance of early diagnosis and intervention. Further studies with larger cohorts are needed to validate these findings and refine management guidelines.